The Sensitivity of Quarterly Models of Wage Determination to Aggregation Assumptions - J.C.R. Rowley; D.A. Wilton (Queen's University, Department of Economics, 1972)
In his A.E.A. Presidential Address, Tobin points out that due to the continuing controversy over the concept of a stable Phillips curve, the institutional features of the labour market have been largely ignored. Hence, the purpose of this paper is twofold: (1) to present an analytical framework for the empirical investigation of these institutional labour market features, and (2) to present some empirical results demonstrating the gravity of the problem.
Keywords: 330